Understanding the Perceived Attributes and Consequences of Participation in Youth "Rep" Hockey: An Analysis from the Parental Perspective - Chris Chard; Jonathon Edwards; Luke Potwarka (Journal of Applied Sports Management, 2015)
Participation in youth sport has been recognized for myriad developmental benefits. When one considers sport participation, there are a number of different delivery models. Participation can be recreational in nature or competitively driven. Regardless of competitive level, it is important for sport managers to understand the drivers that influence sport participation. Thus, the purpose of the current investigation was to achieve a better understanding of the perceived attributes and consequences of youth representative (rep) sport participation from the perspective of the elite athletes' parents. Parents' perceptions are important given that these individuals are the ultimate decision makers for their children's sport participation. To investigate this purpose, a laddering interview technique was employed. Findings indicate that attributes of youth rep sport participation include structure, competition/challenge, and team environment. Perceived consequences or benefits include learning life lessons (leading to productive citizens), skill development (leading to confidence), discipline/accountability, work ethic, and friendships. The attributes and benefits could be used to develop policies, procedures, and rules/regulations that deliver maximum satisfaction at the youth rep level.
Keywords: laddering interviews; youth sports; sport participation; hockey